Thermal and photochemical degradation of polyurethanes based on renewable materials - Mohd Rus, Anika Zafiah (2006)
In recent years, the use of polymers made from renewable materials has been developed in diverse areas especially in furniture, mattresses, automotive or building components. Polyurethanes (PU's) made from renewable materials are one of the most important groups of polymers because of their versatility and they can be manufactured in a wide range of grades, densities and stiffness. In this project, polymers based on renewable materials such as rapeseed (RS) and sunflower oil (SF) were synthesized and cross-linked with methylene di-/>-phenyl diisocyanate (MDI) to form polyurethanes. Treatment with titanium dioxide (TiCh) was found to affect the physical properties of the polyurethane in a systematic way. As the loadings of TiOj were increased (up to 10% of monomer weight), large strain responses were obtained; thus the stress vs. strain curves plotted by the Instron tensile test showed an increase from 5% to 31%). This study also revealed a remarkable characteristic in the pigmented polymer exhibiting soft - but - tough behaviour at high TiC>2 loading. The DMTA test also showed that the properties of the sample loaded with 10 % TiC>2 increased its tan delta peak (damping factor) from 0.43 to 0.7. The tan delta peak showed that the damping properties of the material were improved markedly upon loading with TiC>2. This is useful since noise is radiated by vibration, and the application of damping materials to the vibrating surface converts the energy into heat, which is dissipated within the damping materials rather than being radiated as airborne noise. Increase in TiC>2 loading also gave a progressive increase of hardness (Shore D) for both RS and SF oil - based polyurethanes. The effect of prolonged exposure to UVB light, in general promotes photodegradation for both RS and SF-based polyurethanes, both neat and also material loaded with TiCh- The photodegradation of the PU's depends on the grade of titanium dioxide. The addition of 10 % Degussa P25 pigment, gives the greater degradation while PUs loaded with 5 % Kronos 2220 show the slowest rates of degradation due to the effect of the coating of this pigment. The photostabiliser Tinuvin 770 also offers high protection from UVB, while the combination of Tinuvin 770 and Degussa P25 gave the highest protection from UVB. Addition of Tinuvin 770 at the stage of preparation of the PUs also greatly reduced the undesirable yellow colouration prevalent during PU syntheses.